Proceedings of the Third International Scientific Conference "Intelligent Information Technologies for Industry" (IITI'18) Volume 2 - Abraham, Ajith; Kovalev, Sergey; Tarassov, Valery; Snasel, Vaclav; Sukhanov, Andrey (Advances in Intelligent Systems and Computing, 2019)
This book contains papers presented in the main track of IITI 2018, the Third International Scientific Conference on Intelligent Information Technologies for Industry held in Sochi, Russia on September 17-21. The conference was jointly co-organized by Rostov State Transport University (Russia) and VŠB - Technical University of Ostrava (Czech Republic) with the participation of Russian Association for Artificial Intelligence (RAAI). IITI 2018 was devoted to practical models and industrial applications related to intelligent information systems. It was considered as a meeting point for researchers and practitioners to enable the implementation of advanced information technologies into various industries. Nevertheless, some theoretical talks concerning the state-of-the-art in intelligent systems and soft computing were also included into proceedings.